Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1039/c0ob00286k
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of heterocyclic enamines with nitrile oxide and nitrilimine precursors

Abstract: Alkylidenepyrrolidines 1, 21, 24 and 26 undergo reactions with nitrile oxides and nitrilimines or their precursors to give a range of novel heterocyclic compounds. With alkylidenepyrrolidine ester 1, nitrolic acids give products in which the liberated nitrous acid reacts with the alkylidenepyrrolidine, followed by two cycloadditions to give adducts 3. In contrast, hydroximoyl chlorides give isoxazoles 10, presumably by cycloaddition/elimination. With hydrazonyl chlorides, simple acylation of the alkylidenepyrr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…In contrast to the reactions of these β-azolyl enamines, similar reactions of β-alkyl enamines as reported by Bujak et al [24] are regioselective and not stereospecific and therefore not concerted. We could propose stepwise (path 1) and concerted (path 2) reaction mechanisms for the formation of isoxazolines 3a–c as depicted in Scheme 3, in accordance with the proposed reaction mechanisms of heterocyclic enamines proposed earlier by Elliott and co-workers [36]. Path 1 includes the formation of intermediate A as a result of the electrophilic substitution of the β-H atom of the enamines 1a,b after treatment with hydroxamoyl chlorides 2a,d,g .…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…In contrast to the reactions of these β-azolyl enamines, similar reactions of β-alkyl enamines as reported by Bujak et al [24] are regioselective and not stereospecific and therefore not concerted. We could propose stepwise (path 1) and concerted (path 2) reaction mechanisms for the formation of isoxazolines 3a–c as depicted in Scheme 3, in accordance with the proposed reaction mechanisms of heterocyclic enamines proposed earlier by Elliott and co-workers [36]. Path 1 includes the formation of intermediate A as a result of the electrophilic substitution of the β-H atom of the enamines 1a,b after treatment with hydroxamoyl chlorides 2a,d,g .…”
Section: Resultssupporting
confidence: 89%
“…This kind of cyclization was ruled out by Elliott et al [36] because of a disfavored 5- endo -trig cyclization for the corresponding intermediate oxime.…”
Section: Resultsmentioning
confidence: 99%
“…Microfilaria were used as a preliminary screen for efficacy because they are known to be more sensitive to oxidative stress compared to adults. 11,12 Previous work demonstrated that 1 was active at 10 μM using arsenateinduced ROS formation against both adult and microfilarial forms of B. malayi, 8 and lower concentrations of 1 did not inhibit parasite motility. 8 In this work, copper was employed to generate ROS, and in the heat map shown in Table 3, 1 shows microfilarial activity comparable to arsenate-mediated conditions.…”
mentioning
confidence: 97%
“…In Scheme , commercially available thiomethyl pyrimidine 5 was deprotonated and reacted with commercially available Weinreb amide N -methoxy- N -methylacetamide affording a 43% yield of methyl ketone 6 . Following isoxazole formation with chlorophenyl oxime 7 , , the resulting sulfide was smoothly converted to sulfone 8 using oxone. Sulfone displacement by amines was accomplished in a straightforward manner in DMF at elevated temperature for up to 5 h, affording the Boc-protected intermediates 9a – h in good yield.…”
mentioning
confidence: 99%
See 1 more Smart Citation